Construction of leaf-like CuO–Cu2O nanocomposites on copper foam for high-performance supercapacitors. Issue 10 (23rd February 2017) - He, Dong; Wang, Guanda; Liu, Guolong; Suo, Hui; Zhao, Chun
Abstract : Leaf-like CuO–Cu2 O nanosheets have been prepared on copper foam by a one-step simple anodization method, which can be used as an advanced binder-free supercapacitor electrode. Abstract : Leaf-like CuO–Cu2 O nanosheets have been prepared on copper foam by a one-step simple anodization method, which can be used as an advanced binder-free supercapacitor electrode. The performance of the CuO–Cu2 O/Cu foam electrode was optimized through controlling and restraining the current density and reaction time. The prepared electrode exhibits a very high specific capacitance (1.954 F cm −2 at a scan rate of 2 mV s −1 ), excellent durability (120% retention after 5000 cycles), remarkable rate capability (91.8% retention upon increasing the current density by 10 times) and good coulombic efficiency (78.2% at a current density of 2 mA cm −2 ). The facile and cost-effective fabrication process is also suitable for large scale practical production. These results indicate the leaf-like CuO–Cu2 O/Cu foam electrode would be a promising electrode for high-performance supercapacitor applications.